T-cell activation Rho GTPase-activating protein maintains intestinal homeostasis by regulating intestinal T helper cells differentiation through the gut microbiota - He, Ruirui; Chen, Jianwen; Zhao, Ziyan; Shi, Changping; Du, Yanyun; Yi, Ming; Feng, Lingyun; Peng, Qianwen; Cui, Zhihui; Gao, Ru; Wang, Heping; Huang, Yi; et al. (Frontiers in Microbiology, 2023)
Common variants of the T-cell activation Rho GTPase-activating protein (TAGAP) are associated with the susceptibility to human inflammatory bowel diseases (IBDs); however, the underlying mechanisms are still unknown. Here, we show that TAGAP deficiency or TAGAP expression downregulation caused by TAGAP gene polymorphism leads to decreased production of antimicrobial peptides (AMPs), such as reg3g, which subsequently causes dysregulation of the gut microbiota, which includes Akkermansia muciniphila and Bacteroides acidifaciens strains. These two strains can polarize T helper cell differentiation in the gut, and aggravate systemic disease associated with the dextran sodium sulfate-induced (DSS) disease’s phenotype in mice. More importantly, we demonstrated that recombinant reg3g protein or anti-p40 monoclonal antibody exerted therapeutic effects for the treatment of DSS-induced colitis in wild-type and TAGAP-deficient mice, suggesting that they are potential medicines for human IBD treatment, and they may also have a therapeutic effect for the patients who carry the common variant of TAGAP rs212388.